Probable Sudden Unexpected Death in Dogs With Epilepsy (pSUDED) - Huenerfauth, Enrice; Nessler, Jasmin; Erath, Johannes; Tipold, Andrea (Frontiers in Veterinary Science, 2021)
Sudden unexpected death in human epileptic patients (SUDEP) is defined as death related to recurrent unprovoked seizures, death is occurring unexpectedly and suddenly in a patient with reasonable state of health, without an obvious medical cause of death, trauma, asphyxia or intractable status epilepticus, in post mortem examination no obvious reason for death can be found. “Probable SUDEP” (pSUDEP) is defined as SUDEP not confirmed pathologically. The adapted abbreviation for dogs is used in the following: “pSUDED” (probable sudden unexpected death in dogs with epilepsy). The aim of the present monocentric retrospective study using an online questionnaire was to evaluate the occurrence of pSUDED. Data of canine patients presented with seizures between 01/1998 and 05/2018 were retrospectively analyzed and classified according to their aetiology (n = 1503). Owners were contacted by telephone to participate in answering a validated questionnaire. 509 owners were reached, 373 owners completed the questionnaire. In addition to signalement (e.g. breed), special attention was paid to the frequency and presentation of seizures and seizures in the context of death. Fifty-one percent (191/373) of the dogs were dead at the endpoint of the study. A large proportion of the dogs was euthanized (149/191) because of seizure severity or health problems unrelated to seizures. Idiopathic Epilepsy (IE) was diagnosed in 19/34 dogs which died unexpectedly. Of these seven animals had to be excluded for further investigation of pSUDED because of status epilepticus or aspiration pneumonia as a result of the seizures. In 12 dogs with IE the last seizure event occurred between 6 hours and approximately 3 months before death. pSUDED was suspected in these dogs and an incidence rate of 4.5 - 10 % was calculated. pSUDED occurs in a similar incidence rate as human SUDEP and should be considered as a possible complication in epileptic dogs. The results of this study suggest that dogs with IE but especially those with brachycephalic syndrome and cluster seizures have an increased risk to die of pSUDED. Owners of dogs with seizures should be educated about the risk of sudden death in dogs with epilepsy.